(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
In our paper we present a study in which we investigated the level of information literacy of first-year students across different studies offered by faculties at the University of Graz. Data were collected by means of a multiple-choice questionnaire. In total we analyzed 232 questionnaires completed by first-year students from six studies (faculties). The results show that the overall level of information literacy is mediocre. However, the difference in the level of information literacy across the studies is not as big as originally expected. The type of high school completed has a strong effect at least in the beginning of the studies. Another interesting result shows that the students rated their information literacy skills much higher than the test indicated. It can be concluded that multiple-choice questionnaires are an efficient and objective test instrument to inform the students that they are much less information literate than they believe themselves to be.